Effect of calcination temperature on the humidity sensitivity of TiO2/graphene oxide nanocomposites. (January 2019) - Luo, Liming; Yuan, Mingliang; Sun, Hongjuan; Peng, Tongjiang; Xie, Tangfeng; Chen, Qichao; Chen, Jungang
Abstract: The humidity sensitive elements of TiO2 /Graphene oxide nanocomposites (TGOs) were obtained by interdigital Ag-Pd electrode substrate. The resistance-temperature characteristic and humidity sensitivity of TGOs humidity sensors were characterized by voltammetry in the range of 25–80 °C and between a relative humidity of 11.3–93.6%RH. The results indicated that the calcination temperature obviously affected the resistance variation of the humidity sensitive elements. It can be seen that the resistance of TGOs humidity sensors decreased firstly and then increased with increasing calcination temperature. Meanwhile, the activation energy increased from 12.47 kJ/mol to 54.47 kJ/mol, then decreased to 16.72 kJ/mol, and finally increased to 19.66 kJ/mol. The resistance gradually reduced with the increase in environmental humidity for TGOs humidity sensitive elements calcined at 300 °C. The resistance of TGOs humidity sensors calcined at 350, 400, 450 and 480 °C increased first and then decreased with increasing environmental humidity. The humidity hysteresis of TGOs humidity sensors calcined at 300 °C increased to a maximum value of 24.33%, and decreased to 6.02% at 450 °C. Particularly, TGOs humidity sensors showed p-type nature of the semiconductors in the low RH range (< 62.1%RH) and showed n-type nature of the semiconductors in the high RH range (> 62.1%RH).